Pengembangan Modul Fisika Berbantuan Teknologi Augmented Reality pada Materi Gelombang Bunyi untuk SMA/MA Kelas XI - Lilin Nazwa Khunaeni; Wenty Dwi Yuniarti; Muhammad Ardhi Khalif (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
This research aims to determine the appropriateness of a physics module with Augmented Reality (AR) technology. This research is an RD research consisting of the initial study stages, planning, development, product assessment, product revision and field trials. Data collection techniques used were observation and interviews during the preliminary study, and questionnaires for validation of material experts and media experts, validation of physics teachers, and student responses. Based on the data analysis, it was concluded that the quality of the physics module was very good with a percentage value of 95% from material experts, 86.67% from media experts and 90% from physics teachers. Student responses to the physics module obtained a percentage of 89% in the very good category. Based on the research results, the physics module with Augmented Reality (AR) technology developed is appropriate and can be used in physics learning.